Feasibility of a pilot intervention to reduce pain and syncope during adolescent vaccination. Issue 27 (22nd June 2018) - Henninger, Michelle L.; Kuntz, Jennifer L.; Firemark, Alison J.; Varga, Alexandra M.; Bok, Karin; Naleway, Allison L.
Abstract: Purpose: Vaccines recommended for adolescents are considered safe and effective, however administration may occasionally result in acute pain at the injection site or syncope (fainting). These adverse effects pose a risk to patient safety and are potential barriers to adherence to future vaccinations. We assessed a novel intervention designed to help prevent acute pain and syncope associated with adolescent vaccinations. Methods: We conducted a 3-month pilot study to assess the feasibility and acceptability of a vaccination comfort menu within two Kaiser Permanente Northwest pediatric clinics. The menu offered a variety of comfort items (e.g., cold packs, squeeze balls) that children could select prior to their vaccination. We surveyed parents of recently vaccinated adolescents and interviewed providers to assess the implementation and effectiveness of the intervention. Results: Response rate for the parent survey was 33% (378/1136). Only 20% of the parents reported that their provider offered the comfort menu during the vaccination visit. Approximately 50% of the adolescents who were offered the menu selected a comfort item and most of these participants reported that the item was very (35%) or somewhat (38%) helpful in improving their vaccination experience. Per provider interviews, common barriers to implementing the intervention included lack of time and convenience, and the brevity of the pilot period. Conclusions: The comfort menu may improve the vaccination experience of youth and increase the likelihood of adherence with future vaccinations. However, only 20% of the parents reported that their provider offered the menu during the vaccination visit. Additional research is needed to determine the feasibility of implementing this intervention on a larger scale, as well as assessing whether the intervention has a significant impact on reducing adverse events.